Findings of Exploration Laparotomy: Abdominal Tumors. Reported Experience - Godínez, Jennifer Itzel Jacobo; Hernández, Julio Geovany Flores; Valiente, Mariana González; García, Baruj Ricardo Lupio; Vargas, Astrid Ortiz; Longines, Fabian Cazares; Norman, Armando Hans Torres; Godínez, Elizabeth Xitlali Jacobo; González, Mireya Fuente; Sánchez, Morelos Adolfo García; Carrillo, Carol Atzimba Zepeda (British Journal of Healthcare and Medical Research, 2023)
Emergency surgery is a diagnostic-therapeutic challenge in patients with acute abdomen. Exploratory Laparotomy is defined: "invasive surgical procedure, which seeks to explore the abdominal cavity, for diagnostic and/or therapeutic purposes, thus offering the opportunity to provide rapid and timely treatment to the patient." Objective: to describe the experience of exploratory laparotomies in patients with acute abdomen, and where the unexpected diagnostic finding was abdominal tumors. Patients and Methods: the study had a longitudinal, retrospective, observational and descriptive design. The records of all patients surgically treated for clinically expressed acute abdomen with the support of laboratories and cabinet, in a second level medical care hospital, are reviewed. Results: the patients who underwent emergency exploratory laparotomy 1,277 surgeries in 5 years, of which a total of 135 patients were included. Surgical complications due to the initial etiology of the oncological disease with respect to being locally advanced and/or extremely metastatic (carcinomatosis). Morbidity is 23% and mortality reaches 13%. Discussion: acute abdomen due to oncological etiology is real and it is necessary to avoid nihilism both by the surgeon and the patient, which does exist and should be considered as a possibility. The most common surgical emergency: gastrointestinal obstruction (43%), intra-abdominal inflammatory complications (33%) and bleeding (17%). Conclusions: individualizing the patient according to: the surgical urgency, the oncological pathology, the general conditions of the patient, the infrastructure and the competence of the surgeon; forming a strategy maximizing survival, quality of life and prognosis for each patient.